2019
DOI: 10.1029/2019gl083723
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Percolation Threshold in Muds and Mudrocks During Burial

Abstract: Muds and mudrocks are important barriers to flow and perform this role over their entire depositional history, from mediating sediment‐ocean methane exchange to preventing leakage from hydrocarbon reservoirs, CO2 sequestration targets, or nuclear waste repositories. It is well established that the percolation threshold, which is the fluid saturation at which percolation occurs, is directly related to the pressure sealing capacity of a mud or mudrock. However, the evolution of the percolation threshold during b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 106 publications
0
6
0
Order By: Relevance
“…Marine sediments can also function as a physical sink for CH 4 released from gas hydrate dissociation. There exists a percolation threshold, which is the threshold of gas saturation to show percolation behavior. Thus, large amounts of gas will be trapped and cannot flow freely in the sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Marine sediments can also function as a physical sink for CH 4 released from gas hydrate dissociation. There exists a percolation threshold, which is the threshold of gas saturation to show percolation behavior. Thus, large amounts of gas will be trapped and cannot flow freely in the sediments.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Brooks‐Corey parameterization of the capillary drainage curve: Pnormalc(Sw)=Pnormale(SnormalwSwi1Swi)1λ, where S w is the wetting phase saturation (assumed to be water), S w i is the irreducible wetting phase saturation, P e is the capillary entry pressure, and λ is the pore‐size parameter (Brooks & Corey, 1964). To constrain the Brooks‐Corey parameters ( P e , S w i , and λ ), we used previously published MICP measurements performed on natural and resedimented samples of marine muds from various locations around the world (Daigle & Dugan, 2014; Daigle et al., 2019; Reece et al., 2013; Sawyer et al., 2008; Schneider, 2011). The Brooks‐Corey parameters are expected to vary with grain size and porosity.…”
Section: Methodsmentioning
confidence: 99%
“…This would be more likely in sediments with lower permeability, but understanding this process completely requires detailed models of multiphase flow, which are beyond the scope of the present work. Note that using a 10% mobility threshold will give more conservative estimates of fracturing behavior than using the percolation threshold, which is considerably larger than 10% in shallow marine muds (Daigle et al., 2019). Future research should investigate gas mobility thresholds specific to marine muds, and how this threshold varies during burial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we have a poor understanding of critical gas saturation in shallow sediment. Daigle et al (2019) suggested that critical gas saturation varies with porosity and is high (10-60%) in shallow marine muds. However, they also pointed out that the shallow sediment is the weakest and most prone to tensile fracturing (Boudreau, 2012), which would allow gas escape at lower saturations (Daigle et al, 2019).…”
Section: Lithologymentioning
confidence: 99%